2014
DOI: 10.1007/s00262-014-1559-2
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically de-sialylated CD103+ CD8 T cells mediate beneficial anti-glioma immune responses

Abstract: Taken together, these findings suggest that de-sialylation of CD8 is required for hyper-responsiveness and beneficial anti-glioma activity by CD8 T cells. Because CD8 de-sialylation can be induced with exogenous enzymes (and appears particularly scarce on human T cells), it represents a promising target for clinical glioma vaccine improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…Several studies have demonstrated that the interaction between E-cadherin expressed on epithelial cells and CD103 expressed on lymphocytes plays an important role in the retention of antigen-specific lymphocytes within epithelial tissue [1719]. Thus, we analyzed and compared E-cadherin expression in tumor cells with respect to the number of intratumoral CD103 + TILs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that the interaction between E-cadherin expressed on epithelial cells and CD103 expressed on lymphocytes plays an important role in the retention of antigen-specific lymphocytes within epithelial tissue [1719]. Thus, we analyzed and compared E-cadherin expression in tumor cells with respect to the number of intratumoral CD103 + TILs.…”
Section: Resultsmentioning
confidence: 99%
“…Under homeostasis, CD103 + expression in memory T cells residing in peripheral tissues, including the skin and mucosa, increases the migration and retention of these cells [15, 16]. Moreover, the interaction between CD103 and E-cadherin is responsible for the recruitment and retention of antigen-specific TILs in gliomas, and ovarian cancer, and lung cancer [1719]. CD103 expression was observed more frequently in the TILs of intratumoral (i.e., intraepithelial) than stromal regions, and this has been implicated in patient survival [2022].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a previous study reported that desialylation of CD8 + T cells is required and adequate for T cell effective anti-tumor response against glioma cancer. [42] Thus, future studies at molecular level are envisaged to better understand how sialidase treatment improves anti-tumor mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, one of our groups first demonstrated that an enhanced CD103 + TIL subset correlates with improved early-stage non-small-cell lung carcinoma (NSCLC) patient survival [27]. The predictive value of T RM was also demonstrated in ovarian, breast and bladder cancers [26, 28, 64, 88]. Indeed, in a large cohort of high-grade serous ovarian cancers, CD103 + TIL were associated with improved patient survival [26].…”
Section: Role Of Trm In Immune Surveillance and Immunotherapymentioning
confidence: 99%